Rhodium-Catalyzed Asymmetric Hydrogenation of N-(1-benzylpiperidin-3-yl)-enamides: An Efficient Access to Valuable Enantioenriched 3-Aminopiperidine Derivatives - Royal, Titouan; Dudognon, Yohan; Berhal, Farouk; Bastard, Yvon; Boudet, Bernard; Ayad, Tahar; Ratovelomanana-Vidal, Virginie (Synlett, 2016)
An efficient synthetic entry to enantioenriched 3-aminopiperidine derivatives using rhodium-catalyzed asymmetric hydrogenation of N-(1-benzylpiperidin-3-yl)enamides is described. This method provides an atom-economical and attractive route to both enantiomers of the valuable 3-aminopiperidine moiety, which is an important structural unit that can be found in many natural products and pharmaceutical drugs encompassing a broad range of biological activities. Under optimized reaction conditions, the targeted 3-aminopiperidine derivatives were obtained in high yields up to 92% and with enantiomeric excesses up to 96% after a single crystallization.
Keywords: rhodium; asymmetric hydrogenation; enamide; synphos; 3-aminopiperidine